Phenomenology and nursing: some reflections - Spíndola, Thelma (Revista da Escola de Enfermagem da USP, 1997)
The project is about phenomenology and its elements. It points out the essential ideas of existential phenomenology interpreted by Maurice Merleau-Ponty's ideas and tries to conect this philosophy to nursing world.